Sleep Aids in Elite Athletes: A Narrative Review - Mirkowski, Krzysztof; Miroński, Adam; Minik, Bartosz; Częczek, Kacper; Cieślewicz, Karolina; Szymańska-Zdyb , Kinga; Nowaczek, Patrycja; Braksal, Barbara; Szurek, Zuzanna; Chyła, Zofia (Quality in Sport, 2026)
Background. Sleep is essential for recovery, cognitive performance, and mental health in competitive sport. Athletes may use sleep aids when insomnia, travel fatigue, jet lag, or pre-competition arousal interfere with rest. Aim. This narrative review summarizes current evidence on melatonin, sedative-hypnotics, and related sleep aids in competitive and elite athletes, including their effects on sleep, performance, safety, and anti-doping risk. Material and methods. PubMed, PubMed Central, Google Scholar, and publisher websites were searched in May 2026. Open-access reviews, clinical trials, consensus statements, and official anti-doping documents were prioritized. Results. Current evidence supports structured sleep assessment and non-pharmacological strategies as first-line management. Melatonin appears most relevant for circadian misalignment and travel-related sleep disruption, although direct performance benefits remain uncertain. Evidence regarding classical hypnotics in athletes is limited, while residual sedation, psychomotor impairment, misuse, and dependence remain important concerns. Supplement contamination and variable product quality may also create anti-doping risks. Conclusions. Sleep aids should be used selectively, for clearly defined indications, and under medical supervision. Sleep management in athletes should prioritize behavioral, circadian, and organizational interventions before pharmacological treatment.